Numerical simulation of heat transfers on a circular cylinder by an impinging jet with nanofluid - Jaber Al-Talqani, Ayad Jasim (2014)
Impinging jets are a best method of achieving particularly high heat transfer over a surface circular cylinder, flat plate and concave surface are subjects of interest in many research studies over the past decades. In terms of cooling surfaces in many engineering applications had been devised to enhance the heat transfer from the jet impingement to the target surface. In this work, a study was conducted to investigate numerically related to the jet impingement on a circular cylinder. The objective of this study is to analyze the form and nature of the distribution of heat transfer on the surface of a circular cylinder are bombarded with water and "nanofluid" as a fluid jet. Increase the heat transfer rate by using three types of "nanofluids"namely,(water+Al2O3), (water+ CuO) and (water + SiO2) as a fluid jet impingement also studied.. Effects of different Reynolds numbers (Red) in based nozzle different the ranges of (10000-30000) the performance of jet impingement heat transfer using a water jet impingement will be compared with that using "nanofluids" as the working fluid. Simulations are carried out in the form of dimensional (3-D) and in a "steady state" by using ANSYS 14.0 software that has been commercialized in the market. The results obtained from numerical simulations of jet impingement cooling the cylinders on the heated cylindrical tube will be presented. Heated surface of the cylinder tube will be maintained in a state of "Konstant heatflux". Geometric parameters such as the non-dimensional distance between the tip "nozzle" and the surface of the cylinder tube (h / d) was investigated in the amount of 4.8 and 12.Variasi Nusselt numbers (Nud) along the circumferential and axial directions obtained from this study will be reported along with numerical the flow characteristics of jet impingement. It has been observed mainly in the areas of impact that Nud increased when h/d decreases. (Nud) increased by 21% when the distance ratio h/d = 4 compared with the distance ratio h/d = 12.